Negative and positive consequences of adolescent cancer 10 years after diagnosis: an interview‐based longitudinal study in Sweden. Issue 11 (15th April 2014) - Lehmann, Vicky; Grönqvist, Helena; Engvall, Gunn; Ander, Malin; Tuinman, Marrit A.; Hagedoorn, Mariët; Sanderman, Robbert; Mattsson, Elisabet; von Essen, Louise
Abstract Objective The aim of this study was to provide insight into survivor‐reported negative and positive consequences of cancer during adolescence 10 years after diagnosis and compare these with consequences reported 3 and 4 years after diagnosis. Methods Three, 4, and 10 years after diagnosis, survivors of adolescent cancer were interviewed about negative and positive consequences due to their cancer experience. Manifest content analysis was used to identify categories of reported consequences. Categories of consequences 10 years after diagnosis were compared with consequences reported 3 and 4 years after diagnosis. Results Seven categories of negative consequences were identified: bodily concerns, existential thoughts about loss and life (new at 10 years), psychological problems, difficulties interacting with others, health worries (new), fertility concerns (new), and frustrations about health care (new); and six categories of positive consequences: positive view of life, positive view of self, compassion for others (new), close relationships, gained knowledge about disease and health care, and financial gains. Consistent with previous time points, bodily concerns were reported most often. The majority of survivors (n = 22) reported both negative and positive consequences of their former disease. Few reported only negative (n = 2) or only positive consequences (n = 4). Conclusions Ten years after diagnosis, most survivors reported both negative and positive consequences. New themes, relevant to young adulthood and long‐term survival, were identified. Health care professionals treating young adult survivors may anticipate and address problems regarding physical health, fertility, and health care but may also reinforce positive affect by addressing survivors' positive views of life, sense of self, and close relationships. © 2014 The Authors. Psycho‐Oncology published by John Wiley & Sons, Ltd.